1998
DOI: 10.1161/01.str.29.3.705
|View full text |Cite
|
Sign up to set email alerts
|

Calcium in Ischemic Cell Death

Abstract: Background-This review article deals with the role of calcium in ischemic cell death. A calcium-related mechanism was proposed more than two decades ago to explain cell necrosis incurred in cardiac ischemia and muscular dystrophy. In fact, an excitotoxic hypothesis was advanced to explain the acetylcholine-related death of muscle end plates. A similar hypothesis was proposed to explain selective neuronal damage in the brain in ischemia, hypoglycemic coma, and status epilepticus. Summary of Review-The original … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
438
1
7

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 737 publications
(459 citation statements)
references
References 177 publications
(150 reference statements)
13
438
1
7
Order By: Relevance
“…The major cause of cell death in the ischemic tissue is an uncontrolled elevation of intracellular [Ca 2+ ] [6][7][8]. In the core, levels of extracellular Ca 2+ drop from ~2 mM to 0.05-0.08 mM, reflecting major Ca 2+ movement into the intracellular space.…”
Section: Introduction: Overview Of Ischemic Brain Damagementioning
confidence: 99%
“…The major cause of cell death in the ischemic tissue is an uncontrolled elevation of intracellular [Ca 2+ ] [6][7][8]. In the core, levels of extracellular Ca 2+ drop from ~2 mM to 0.05-0.08 mM, reflecting major Ca 2+ movement into the intracellular space.…”
Section: Introduction: Overview Of Ischemic Brain Damagementioning
confidence: 99%
“…Specifically, it has been reported that glutamate-induced neurotoxicity depends on mitochondrial Ca 2+ uptake ([Ca 2+ ] m ) [9,12]. Under stress conditions, there is an early increase in [Ca 2+ ] m that may contribute to mitochondrial dysfunction [13,14] and MPTP opening, a point-of-no-return step in the intrinsic pathway of apoptotic cell death [15,16].…”
mentioning
confidence: 99%
“…Kainic acid is known to cause an increase in the levels of extracellular glutamate, [47][48][49] and the excitotoxicity of this amino acid is commonly related to the neuronal death observed for both neurodegenerative disorders and acute brain injuries. 45,46 Owing to its neuroprotective effects, biologically delivered NGF has been reported to counteract the death of striatal neurons, caused by excitotoxic insults. [60][61][62] In this work, we investigated the potential of Tf-lipoplexes (prepared at the 8/1 (+/À) lipid/DNA charge ratio) to mediate both neuronal protection and regeneration upon delivery of the NGF gene.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44] Neuronal cell death is thought to be due, at least in part, to the massive influx of calcium induced by overactivation of glutamate receptors. 45,46 Kainic acid, an agonist of AMPA receptors, is responsible for the initiation of an excitotoxic cascade, which results in the accumulation of excitatory amino acids, such as glutamate, and thus in the increase of intracellular calcium concentration. [47][48][49] Therefore, kainic acid has commonly been used to elicit a selective neurodegeneration, both in vitro 48 and in vivo.…”
Section: Effect Of Ngf Expression On An In Vivo Model Of Excitotoxic mentioning
confidence: 99%